Complete Controllability of Impulsive Fractional Linear Time-Invariant Systems with Delay - Xian-Feng Zhou; Song Liu; Wei Jiang (Abstract and Applied Analysis)
Some flaws on impulsive fractional differential equations (systems) have been found. This paper is concerned with the complete controllability of impulsive fractional linear time-invariant dynamical systems with delay. The criteria on the controllability of the system, which is sufficient and necessary, are established by constructing suitable control inputs. Two examples are provided to illustrate the obtained results.